Pelatihan Pembuatan Media Video Promosi Penjualan Dodol Di Desa Lama Hamparan Perak - Dani Manesah; Muhammad Ali Mursid Alfathoni (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2021)
Old Village is located in one of the Districts of Hamparan Perak, Deli Serdang Regency of North Sumatra Province. The activities carried out by Mr. Sabarudin and some members in the Old Village of Hamparan Perak are producing traditional dodol-type food. Although only traditional food but the food is no less competitive amid popular food in the community. But there is one problem that is related to the promotion carried out by Mr. Sabarudin and members, still using manual methods and only done by word of mouth only. The methods used in this devotion are observation, interview, approach and training. With the application of these methods aims to facilitate in the process of community service implementation in the creation of promotional videos. The implementation stage of the activity starts from the preparation stage of implementation, and evaluation that focuses on skills in making a sales promotion using video media. The results obtained in activities and training in the use of video media as a means of promotion are to increase absorption and income for Mr. Sabarudin and members. Before this training was held the promotion of dodol was only by word of mouth. This community service activity is useful for dodol making business actors in the Old Village of Hamparan Perak Subdistrict.